MLL fusion proteins and transcriptional control - Slany, Robert (Biochimica Et Biophysica Acta-Gene Regulatory Mechanisms, 2020)
The highly leukemogenic MLL fusion proteins have a unique mechanism of action. This review summarizes the current knowledge of how MLL fusions interact with the transcriptional machinery and it proposes a hypothesis how these proteins modify transcriptional control to act as transcriptional amplifiers causing runaway production of certain RNAs that transform hematopoietic cells.
CRIS-Team Scopus Importer:2020-03-06